Stereotypes of older adult lesbians and gay men - Wright, Sara L., author; Canetto, Silvia, advisor; Byrne, Zinta, committee member; Asmus, Cheryl L., committee member; MacPhee, David, committee member (Colorado State University. Libraries, 2005)
Past research has examined stereotypes of sexual orientation-unspecified adult and older adult women and men. There has also been research on stereotypes of age-unspecified lesbians and gay men. No research to date, however, has formally focused on stereotypes of older adult lesbians and gay men. This study examined stereotypes of older adult (age 65) lesbians and gay men as compared to stereotypes of older adult heterosexual women and men and stereotypes of adult (age 35) sexual minority and heterosexual women and men. It also considered the possible relationship of the sex and gender ideology of the respondent to stereotyping. On attributes reflecting conventionally feminine and masculine physical characteristics, role behaviors, and traits, target gender and target sexual orientation together were most related to perceptions. Both 35- and 65-year-old heterosexual women were viewed in similar ways, but different from heterosexual men. However, 35- and 65- year-old lesbians were perceived as similar to 35- and 65-year-old heterosexual men in terms of conventional masculine traits, while 35- and 65-year-old gay men were believed to be like 35- and 65-year-old heterosexual women in terms of conventional feminine and masculine physical characteristics and traits. Stereotypes of gay men were more distinct than stereotypes of lesbians. When age-linked attributes were examined, the age of the target appeared to be most related to stereotypes, as compared to the sex of the target or the sexual orientation of the target. Specifically, older adult sexual minorities were perceived as similar to older adult heterosexuals on age-related attributes reflecting health and energy. At the same time, older adult sexual minorities were considered different from older adult heterosexuals on attributes reflecting judiciousness, instrumental role behaviors, and conventional feminine physical characteristics. Respondent sex and respondent gender ideology had minimal influence on the content of stereotypes. These findings point to the necessity of considering the relationships among target gender, age, and sexual orientation when conceptualizing gender and aging stereotypes.
Keywords: social psychology; women's studies; gerontology; LGBTQ studies